Self-consolidating concrete incorporating palm oil fuel ash as a supplementary cementing material / Mohd Hafizan Md. Isa - Mohd Hafizan , Md. Isa (2013)
This thesis presents the development of self-consolidating concrete (SCC) incorporating palm oil fuel ash (POFA) as a supplementary cementing material (SCM). Different SCC mixtures were produced based on the water/binder (W/B) ratios of 0.40, 0.50 and 0.60. POFA was incorporated in concretes substituting 0%, 5%, 10%, and 15% of normal portland cement by weight. The freshly mixed concretes were tested for filling ability, passing ability, and segregation resistance. The filling ability was determined with respect to slump flow, T50cm spread time, and V-funnel flow time. The passing ability was measured with regard to J-ring flow. The segregation resistance was examined by sieve and column tests. Test results showed that the slump flow and J-ring flow decreased whereas the T50cm spread time and V-funnel flow time increased with higher POFA content. The reduced slump flow and J-ring flow were still in the acceptable range. In addition, the segregation index and segregation factor obtained from sieve and column tests, respectively, decreased with greater POFA content. The hardened concretes were tested for compressive strength, ultrasonic pulse velocity, water absorption, and permeable porosity. The effects of water to binder (W/B) ratio of POFA content on the hardened properties of concrete were observed. The correlations of compressive strength with ultrasonic pulse velocity and permeable porosity were also identified. According to test results, the compressive strength and ultrasonic pulse velocity decreased while the water absorption and permeable porosity increased with higher W/B ratio. POFA was not effective in improving the hardened properties of concretes produced with the W/B ratios of 0.50 and 0.60. However, significant improvement was observed when POFA was used in concrete with the W/B ratio of 0.40. The optimum POFA content was 5% in the context of present study.